Anti-biofilm activities of essential oils rich in carvacrol and thymol against Salmonella Enteritidis. Issue 3 (16th March 2019) - Čabarkapa, Ivana; Čolović, Radmilo; Đuragić, Olivera; Popović, Sanja; Kokić, Bojana; Milanov, Dubravka; Pezo, Lato
Abstract: The aim of the present study was to determine the bioactive compounds in four essential oils (EO's) from Origanum heracleoticum, Origanum vulgare, Thymus vulgaris and Thymus serpyllum and to assess their antimicrobial and anti-biofilm activity against Salmonella Enteritidis. Strains were previously characterized depending on the expression of the extracellular matrix components cellulose and curli fimbriae as rdar (red, dry and rough) and bdar morphotype (brown, dry and rough). This study revealed that the EO's and EOC's (carvacrol and thymol) investigated showed inhibition of biofilm formation at sub-minimum inhibitory concentration. Comparing the efficacy of EO's and EOC's in the inhibition of biofilm formation between the strains with different morphotype (rdar and bdar) did not show a statistically significant difference. Results related to the effectiveness of EO's and EOC's (the essential oil components, carvacrol and thymol) on eradication of preformed 48 h old biofilms indicated that biofilm reduction occurred in a dose-dependent manner over time.